The International Finance Corporation’s and Multilateral Investment Guarantee Agency’s Support for Private Investment in Fragile and Conflict-Affected Situations, Fiscal Years 2010–21 : An Independent Evaluation - World Bank (Washington, DC, 2022)
The World Bank Group estimates that, by 2030, up to two-thirds of the world’s extreme poor will live in countries characterized by fragility, conflict, and violence (FCV). The Bank’s FCV strategy emphasizes the critical role the private sector plays in providing jobs and income in fragile and conflict-affected situations (FCS) and its importance in contributing to sustainable development in FCS countries. Supporting investments in FCS has been a strategic priority for both the Bank’s International Finance Corporation (IFC) and Multilateral Investment Guarantee Agency (MIGA) for over a decade. In fact, IFC and MIGA adopted ambitious volume targets for investments and guarantees in International Development Association (IDA) and FCS countries. For instance, IFC committed to delivering 40% of its business volume in IDA and FCS countries, and 15–20% in low-income IDA and IDA FCS countries by 2030. MIGA committed to increasing the share of the volume of guarantees issued to projects in FCS and IDA countries to 30– 33% of its guarantee volume by FY23. But despite gradually deploying new tools and instruments in FCS, increasing investments in FCS has been challenging. This evaluation assesses IFC’s and MIGA’s effectiveness in supporting private investment and development impact in Fragile and Conflict-affected Situations (FCS) and identifies key factors constraining private investment in FCS and possible trade-offs that practitioners and policy-makers need to consider. Based on its findings, IEG makes three recommendations to strengthen the relevance and effectiveness of IFC’s and MIGA’s support to investments and private sector development in FCS.